Inúteis e perigosos: o "Diário da noite" e a representação das classes populares - São Paulo 1950-1960 - Romero, Mariza (2009)
The present research intends to uncover the meaning of the social images and representations on popular social groups produced by São Paulo's newspaper Diário da Noite during the 1950's, which undoubtedly created especial bonds between this newspaper and São Paulo's working classes. Owned by Assis Chateaubriand since 1925, it was already in 1950 one of the best selling newspapers of São Paulo. The Diário da Noite defined itself as an instrument of the great popular masses, developing and presenting a sensationalist tone during this period. This newspaper expressed the significant changes of the 1950's, and attended at the same time both popular demands and social claims of the ruling classes in São Paulo. The upper classes saw the rise of popular social sectors on the political scene with apprehension, considering national political integration mainly as economic and technical development associated with international funds, displaying, therefore, a very narrow view on citizenship. The newspaper Diário da Noite employed all the means normally used by sensationalist press and produced representations and images on the popular classes that tended to limit and exclude popular participation in Brazilian politics. People appeared in its pages simultaneously as simple- minded, as victim, as ignorant or dangerous, being seldom represented as a whole of active citizens, fully aware of their duties and rights. The Diário da Noite thus helped to establish the limits of popular political participation in Brazil, linking its images and representations on people with social order's upkeep and maintenance